2005
DOI: 10.1111/j.1365-2885.2005.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and interstitial fluid pharmacokinetics of enrofloxacin, its metabolite ciprofloxacin, and marbofloxacin after oral administration and a constant rate intravenous infusion in dogs

Abstract: Enrofloxacin and marbofloxacin were administered to six healthy dogs in separate crossover experiments as a single oral dose (5 mg/kg) and as a constant rate IV infusion (1.24 and 0.12 mg/h.kg, respectively) following a loading dose (4.47 and 2 mg/kg, respectively) to achieve a steady-state concentration of approximately 1 microg/mL for 8 h. Interstitial fluid (ISF) was collected with an in vivo ultrafiltration device at the same time period as plasma to measure protein unbound drug concentrations at the tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 57 publications
10
71
2
1
Order By: Relevance
“…Therefore, it is necessary to determine the active concentration of free antimicrobial drugs at the target site using PK-PD modeling to achieve a rational dosage regimen. Previous studies have reported the application of an ultrafiltration sampling technique for isolating the free (unbound) drug in the gastrointestinal tract of calves, and in the ISF of different tissues (e.g., intramuscular, subcutaneous, and intrapleural tissues) of calves, sheep, and pigs 27, 28, 30, 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to determine the active concentration of free antimicrobial drugs at the target site using PK-PD modeling to achieve a rational dosage regimen. Previous studies have reported the application of an ultrafiltration sampling technique for isolating the free (unbound) drug in the gastrointestinal tract of calves, and in the ISF of different tissues (e.g., intramuscular, subcutaneous, and intrapleural tissues) of calves, sheep, and pigs 27, 28, 30, 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that FQs could be converted into their epimers in different environments. For example, transformation from EFX to CFX was reported in plant root systems (Liu et al 2013); the biotransformation of CFX and NFX by microorganisms was confirmed (Parshikov et al 2001;Sukul and Spiteller 2007), and the same transformation was even reported in animals (Bidgood and Papich 2005;Fu et al 2008). The transformation to CFX altered the original distributions of EFX and NFX in manure and soil matrix.…”
Section: Discussion Fqs Pollution and Contributory Factorsmentioning
confidence: 83%
“…3 In dogs, approximately 80% of marbofloxacin circulates unbound in the plasma. 34 The drug is only minimally (10% to 15% of the drug dose) metabolized by the liver into 2 main metabolites, N-desmethyl-marbofloxacin and N-oxide marbofloxacin. 35 Forty percent of an orally administered dose of marbofloxacin in dogs is excreted unchanged in the urine, with the remainder excreted unchanged via the bile in the feces.…”
Section: Discussionmentioning
confidence: 99%